Historical and Geographical Basis of Transformations of the Planning Structure of Chernihiv - Запотоцька, Вікторія Анатоліївна; Голуб, Юлія (Київський національний університет імені Тараса Шевченка, 2023)
The transformation of the planning structure of the city of Chernihiv, starting from the 10th century, is analyzed. The peculiarities of the development and construction of the city in the 17th-20th centuries are considered. The main reasons that led to the replanning, reconstruction, expansion of the city, implementation of measures for the improvement of the territory in certain periods of Chernihiv development are outlined. The main features of the modern functional and planning structure of the city are presented. The dangers associated with changing the appearance of the urban space were analyzed, and priority directions for further optimization of the planning structure of Chernihiv were emphasized. The growth of the population, the deepening of their influence on the environment and the scientific and technological revolution caused the emergence of new complex tasks associated with the progressive development of cities. Among them: the acceleration of the rate of urbanization, environmental pollution, changes in the structure of the city's economy, infrastructure complications, an increase in resources and costs to meet the needs of the population, a significant number of potential threats, etc. The relevance and socio-economic value of the study of urban territories contributed to the integration of many scientific disciplines in the direction of creating urban concepts for optimizing the space for the life of the population. The purpose of the article is a historical-geographical analysis of the transformation of the planning structure of Chernihiv. To achieve the goal, the following tasks were selected in the study: consider the transformations of the planning structure of Chernihiv starting from the 10th century; reveal the features of the development and construction of the city in the 17th-20th centuries; outline the main reasons that led to the re-planning, reconstruction, expansion of Chernihiv in different periods of development; find out the main features of the modern functional and planning structure of the city.

Проаналізовано трансформацію планувальної структури міста Чернігова, починаючи з Х ст. Розглянуто особливості розвитку та забудови міста в XVII-XX–ст. Окреслено основні причини, що зумовили перепланування, реконструкцію, розширення міста, здійснення заходів щодо благоустрою території в окремі періоди розвитку Чернігова. Представлено основні риси сучасної функціонально-планувальної структури міста. Проаналізовано небезпеки, пов’язані зі зміною зовнішнього вигляду міського простору, та наголошено на пріоритетних напрямах подальшої оптимізації планувальної структури Чернігова. Зростання чисельності населення, поглиблення їхнього впливу на навколишнє середовище та науково-технічна революція зумовили появу нових складних завдань, пов'язаних із поступальним розвитком міст. Серед них: прискорення темпів урбанізації, забруднення навколишнього середовища, зміни в структурі економіки міста, ускладнення інфраструктури, збільшення ресурсів і витрат на задоволення потреб населення, значна кількість потенційних загроз тощо. Актуальність та соціально-економічна цінність дослідження міських територій сприяла інтеграції багатьох наукових дисциплін у напрямку створення містобудівних концепцій оптимізації простору для життєдіяльності населення. Метою статті є історико-географічний аналіз трансформації планувальної структури Чернігова. Для досягнення мети в дослідженні були виділені такі завдання: розглянути трансформації планувальної структури Чернігова, починаючи з 10 ст.; розкрити особливості розвитку та забудови міста в 17-20 ст.; окреслити основні причини, що зумовили перепланування, перебудову, розширення Чернігова в різні періоди розвитку; з’ясувати основні риси сучасної функціонально-планувальної структури міста.
Історико-географічні засади трансформацій планувальної структури міста Чернігова
Keywords: planning structure; urban transformations; improvement of the territory; urban space; планувальна структура; міські трансформації; благоустрій території; міський простір